Colonial trauma and identity negotiation: A social psychological analysis of racial consciousness in achebe’s novels - Yun Zhang (Environment and Social Psychology, 2025)
This study re-examines Chinua Achebe’s works through social identity theory [1] and cultural trauma theory [2]. The analysis reveals how colonial oppression triggers identity threat [3] and collective self-redefinition [4]. Quantitative analysis of Igbo proverbs’ emotional valence demonstrates cultural trauma encoding; characters like Okonkwo exhibit reactive self-stereotyping [5] under colonial pressure. The intersection of gender and class is analyzed via social identity complexity [6], showing Beatrice’s leadership in Anthills of the Savannah as intersectional resilience through oral tradition appropriation. The research bridges postcolonial literature with social psychology, offering new frameworks for understanding identity reconstruction in postcolonial contexts.